Cybersecurity Risk Assessment Framework for Blockchain-Based Financial Technology Applications - Dinarwati, Dini; Ilham, Muhammad Ghifari; Rahardja, Fransisca (ADI Journal on Recent Innovation, 2025)
The integration of blockchain technology into financial technology (fintech) applications has transformed the financial industry by offering enhanced transparency, efficiency, and trust. However, this integration also introduces complex cybersecurity challenges that could jeopardize data integrity, operational reliability, and user trust. To address these issues, this study aims to develop a Cybersecurity Risk Assessment Framework tailored specifically for blockchain based fintech applications. Using a mixed methods approach, the study com- bines qualitative insights from expert interviews with quantitative risk analysis techniques, including Failure Mode and Effects Analysis (FMEA). This method facilitates the identification and evaluation of critical threats such as smart contract vulnerabilities, consensus mechanism attacks, and unauthorized access to sensitive data. The proposed framework is validated through case studies of existing blockchain-based fintech platforms to assess its practicality and robustness. Results show that the framework effectively identifies and mitigates potential risks, thereby improving system security and operational resilience. This research bridges the gap between theoretical cybersecurity principles and practical fintech applications, providing actionable strategies for industry practitioners and policymakers. The study concludes that adopting the framework enhances the security posture of blockchain-based fintech ecosystems, enabling innovation while safeguarding against evolving cybersecurity threats.